Comparison of ultra-widefield fluorescein angiography with the Heidelberg Spectralis® noncontact ultra-widefield module versus the Optos® Optomap® - Witmer MT (Dove Medical Press, 2013)
Matthew T Witmer, George Parlitsis, Sarju Patel, Szilárd KissDepartment of Ophthalmology, Weill Cornell Medical College, New York, NY, USAPurpose: To compare ultra-widefield fluorescein angiography imaging using the Optos® Optomap® and the Heidelberg Spectralis® noncontact ultra-widefield module.Methods: Five patients (ten eyes) underwent ultra-widefield fluorescein angiography using the Optos® panoramic P200Tx imaging system and the noncontact ultra-widefield module in the Heidelberg Spectralis® HRA+OCT system. The images were obtained as a single, nonsteered shot centered on the macula. The area of imaged retina was outlined and quantified using Adobe® Photoshop® C5 software. The total area and area within each of four visualized quadrants was calculated and compared between the two imaging modalities. Three masked reviewers also evaluated each quadrant per eye (40 total quadrants) to determine which modality imaged the retinal vasculature most peripherally.Results: Optos® imaging captured a total retinal area averaging 151,362 pixels, ranging from 116,998 to 205,833 pixels, while the area captured using the Heidelberg Spectralis® was 101,786 pixels, ranging from 73,424 to 116,319 (P = 0.0002). The average area per individual quadrant imaged by Optos® versus the Heidelberg Spectralis® superiorly was 32,373 vs 32,789 pixels, respectively (P = 0.91), inferiorly was 24,665 vs 26,117 pixels, respectively (P = 0.71), temporally was 47,948 vs 20,645 pixels, respectively (P = 0.0001), and nasally was 46,374 vs 22,234 pixels, respectively (P = 0.0001). The Heidelberg Spectralis® was able to image the superior and inferior retinal vasculature to a more distal point than was the Optos®, in nine of ten eyes (18 of 20 quadrants). The Optos® was able to image the nasal and temporal retinal vasculature to a more distal point than was the Heidelberg Spectralis®, in ten of ten eyes (20 of 20 quadrants).Conclusion: The ultra-widefield fluorescein angiography obtained with the Optos® and Heidelberg Spectralis® ultra-widefield imaging systems are both excellent modalities that provide views of the peripheral retina. On a single nonsteered image, the Optos® Optomap® covered a significantly larger total retinal surface area, with greater image variability, than did the Heidelberg Spectralis® ultra-widefield module. The Optos® captured an appreciably wider view of the retina temporally and nasally, albeit with peripheral distortion, while the ultra-widefield Heidelberg Spectralis® module was able to image the superior and inferior retinal vasculature more peripherally. The clinical significance of these findings as well as the area imaged on steered montaged images remains to be determined.Keywords: peripheral, retina, wide-angle, widefield, ultra-widefield